The Stability, Microstructure, and Microrheological Properties of Monascus Pigment Double Emulsions Stabilized by Polyglycerol Polyricinoleate and Soybean Protein Isolate - Xu, Duoxia; Zheng, Boyan; Che, Yixin; Liu, Guorong; Yuan, Yingmao; Wang, Shaojia; Cao, Yanping (Frontiers in Nutrition, 2020)
Monascus pigment is a natural food pigment and is commonly used for coloring and as antiseptic of cured meat products, confectionery, cakes, and beverages. However, Monascus pigment is sensitive to environmental conditions. The main aim of this study was to investigate the effect of polyglycerol polyricinoleate (PGPR) and soy protein isolate (SPI) on the particle size, zeta potential, physical stability, microstructure, and microrheological properties of Monascus pigment double emulsions. The effects of ionic strength, heating, and freeze thawing treatment on the stabilities of Monascus pigment double emulsions were also characterized. It was found that the optimum PGPR and SPI concentrations for fabricating Monascus pigment double emulsion were 3.6 and 3.0 wt%, respectively. The fabricated Monascus pigment double emulsion was composed of fine particles with narrow and uniform size distributions. Microrheological property results suggested that the elastic characteristic of the Monascus pigment double emulsion was dominated with increasing PGPR and SPI contents. It was mainly due to the increased collision and interaction between the droplets during the movement resulting in force increasing. Monascus pigment double emulsions with <5 mM CaCl2 prevented calcium to destroy the physical stability of emulsions, while Monascus pigment double emulsions with more than 10 mM CaCl2 formed creaming. After freeze thawing treatment, creaming occurred in Monascus pigment double emulsion. However, it was stable against heating treatment due to heating leading to a dense network structure. It could be contributed to the practical applications of Monascus pigment double emulsions in food products.